Synthesis of Smart Packaging Based on Chitosan-PVA/Binahong Extract as an Antibacterial Plastic - Aras, Neny Rasnyanti M; Lestari, Mega Fia; Irwana, Adinda (Hasanuddin University, 2024)
Chitosan-PVA composite with the addition of binahong extract is a bioplastic that is being developed aims to make eco-friendly product and contain antibacterial agents. This bioplastic is useful as packaging to maintain the freshness quality of food. The purpose of this research is to study and develop smart packaging with the addition of binahong leaf extract as an antibacterial agent. The manufacture of plastic in this study was carried out by varying the addition of binahong leaf extract ranging from 60-100%. The characteristics of the chitosan-PVA plastic were tested through FTIR, water uptake, and antibacterial tests. Chitosan-PVA plastic with the addition of 100% concentration of binahong extract had a good bacterial inhibition of 12 mm. The resulting chitosan-PVA plastic with binahong extract showed the presence of chemical bonds between the chitosan, PVA and flavonoid groups. The bioplastics produced have quite a large water uptake compared to non-biodegradable commercial packaging, reaching 491.52% with the addition of 90% binahong extract with the best antibacterial capabilities in the packaging with the addition of 100% binahong extract.